Urgent computed tomography angiography in paediatric stroke. (5th June 2022) - Briest, Romain C.; Cheung, Andrew K.; Kandula, Tejaswi; Cardamone, Michael; Pillai, Sekhar C.; Sampaio, Hugo; Teoh, Hooi‐Ling; Webster, Richard I.; Wenderoth, Jason D.; Andrews, P. Ian
Abstract: Aim: To improve delivery of acute therapies for acute ischaemic stroke (AIS). Method: We identified factors influencing the speed of diagnosis and delivery of acute therapies in a prospective cohort of 21 children with suspected AIS (eight with AIS, 13 stroke mimics) and explored them in a retrospective cohort with confirmed AIS. Results: Approximately half of the prospective and total AIS cohorts presented with acute, sustained hemiparesis, and were diagnosed relatively quickly. AIS was suspected and diagnosed more slowly in the half presenting with symptoms other than sustained hemiparesis. Thirty‐one out of 51 patients with AIS (19 females, 32 males, mean age 8 years 6 months, SD 5 years 4 months) had arterial abnormalities identified by computed tomography angiography (CTA) or magnetic resonance angiography (MRA): 11 with large vessel occlusion, six with dissection, five with moyamoya disease, nine with other arteriopathies. Among these patients, those initially imaged with CTA were diagnosed more quickly than those with initial magnetic resonance imaging/angiography, which facilitated thrombectomy and thrombolytic therapy. Twenty out of 51 had AIS without arterial abnormalities on CTA or MRA: eight with lenticulostriate vasculopathy and 12 with other small‐vessel AIS. Among these patients, 80% were ineligible for thrombolysis for reasons beyond delay to diagnosis, and all showed good outcomes with supportive treatments alone. Interpretation: Clinical features at presentation influence rapidity with which childhood AIS is suspected and diagnosed. Readily available CTA can direct thrombectomy in patients with large vessel occlusion and thrombolysis in most, but not all, eligible patients. What this paper adds: Children with acute ischaemic stroke (AIS) commonly present with symptoms other than sustained hemiparesis. Stroke is more slowly recognized in these patients, which limits potential therapies. Computed tomography angiography (CTA) accurately identifies AIS with large vessel occlusion, enabling timely endovascular thrombectomy. CTA is sufficient to direct thrombolytic therapy in most eligible children. Most childhood AIS without arterial abnormalities identified by CTA had good outcomes. What this paper adds: Children with acute ischaemic stroke (AIS) commonly present with symptoms other than sustained hemiparesis. Stroke is more slowly recognized in these patients, which limits potential therapies. Computed tomography angiography (CTA) accurately identifies AIS with large vessel occlusion, enabling timely endovascular thrombectomy. CTA is sufficient to direct thrombolytic therapy in most eligible children. Most childhood AIS without arterial abnormalities identified by CTA had good outcomes. Clinical features at presentation influence rapidity with which childhood stroke is suspected and diagnosed. Children presenting with dominant symptoms other than hemiparesis are diagnosed slowly, which reduces treatment options. Readily available, urgent computed tomography angiography provides sufficient data to facilitate thrombectomy in children with large vessel occlusion and to direct thrombolysis for most, but not all, eligible patients. This original article is commented on by Tatishvili on pages 14–15 of this issue.